Women of storm surges meaning making as cultural process of social repair for Yolanda survivors - Go, Chaya Ocampo (Quezon City Ateneo de Manila University, 2017)
"Years after Typhoon Yolanda (international code name: Haiyan) struck Leyte island in the Eastern Visaya region in 2013, I conduct a feminist ethnographic research and inquire into the ways Waray women survivors make meaning of this super typhoon and how they mobilize disaster memory and symbolisms in their survival terstimonies to engage in social repair. In showing how the women survivors (a) personify the storm; (b) explain order and safety in cycles and seasons; and (c) explain syncretic theologies pertaining to ideas of justice, I argue that they enact an ancient ferocity as a form of agency for survival."
Keywords: Disasters; Ethnology; Eastern Visayas; Typhoon Yolanda; Feminist ethnography; #aDecolonizing methodology